Regional Structural Differences in Household Consumption in Bulgaria - Damyanov, Dimitar (Research Papers, 2025)
Regional differences are among the frequently discussed issues in Bulgarian economic literature. In this paper we focus on a less common topic in that area – structural differences in household consumption among the six NUTS2 regions of Bulgaria. Comparisons are made between them based on their consumption structures, and a sigma-convergence approach is applied to find out whether a convergence (or divergence) process is taking place. Results show relatively small but increasing differences between regions which can be attributed to differences in income levels and demographic characteristics.
Keywords: Age distribution; Consumption; Consumption structure; Regional convergence